2004
DOI: 10.5194/angeo-22-1317-2004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evolution of magnetospheric current systems during storms

Abstract: Abstract. We present a method to model the storm-time magnetospheric magnetic field using representations of the magnetic field arising from the various magnetospheric current systems. We incorporate the effects of magnetotail changes during substorms by introducing an additional localized thin current sheet into the Tsyganenko T89 model. To represent the storm-time ring current the T89 ring current is replaced by a bean-shaped current system, which has a cross section that is close to the observed distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 33 publications
3
97
0
Order By: Relevance
“…When setting the model boundary at 10 R E and using Tsyganenko magnetic fields, we include the effect from the nearEarth tail current from the stretched magnetic field lines. The results are in agreement with the modeling efforts by Ganushkina et al (2004). They have shown that during moderate storms the tail current intensifies first and tracks the drop in the Dst index.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…When setting the model boundary at 10 R E and using Tsyganenko magnetic fields, we include the effect from the nearEarth tail current from the stretched magnetic field lines. The results are in agreement with the modeling efforts by Ganushkina et al (2004). They have shown that during moderate storms the tail current intensifies first and tracks the drop in the Dst index.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies, however, have suggested that the Dst index contains contributions from many other sources than the azimuthally symmetric ring current (Campbell, 1973;Arykov and Maltsev, 1993;Dremukhina et al, 1999;Alexeev et al, 2001;Ohtani et al, 2001;Liemohn, 2003;Ganushkina et al, 2004;Kalegaev et al, 2005). Based on GOES 8 measurements and their correlation with Dst, Ohtani et al (2001) determined the contribution from the tail current at Dst minimum to be, at least, 25 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of being able to compute the actual (rather than model) value of lies in estimating the adequacy of the model being used and the uncertainties. Multipoint magnetic field data would also allow the use of event-fitted models [e.g., Ganushkina et al, 2004] that could allow the use of the actual first invariant with consistent estimates of the second and third invariants. In the absence of operational event-fitted models, it is necessary to estimate the uncertainty in the estimated arising from the use of the empirical models.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Dst-index contains contributions from many other sources than the azimuthally symmetric ring current and their contributions can be significant or even largest during disturbed conditions. The suggested magnetospheric sources include (1) magnetopause currents, (2) cross-tail current, (3) partial ring current, and even (4) substorm current wedge (see the review by Maltsev 2004 and references therein) and also studies by Friedrich et al (1999), Munsami (2000), Ohtani et al (2001), Liemohn et al (2001a,b), Liemohn (2003), Ganushkina et al (2004Ganushkina et al ( , 2010, Kalegaev et al (2005). The magnetic field measured on the ground contains contributions from all current systems and there is no other way to separate them but to use magnetospheric models.…”
Section: Dst-index As a Storm Indicator Measure And Predictormentioning
confidence: 99%